Metal–organic-framework derived porous conducting frameworks for highly efficient quantum dot-sensitized solar cells. Issue 17 (13th April 2017) - Liu, Yingru; Sun, Yuxiu; Zhang, Jingbo
Abstract : Metal–organic-framework (MOF) derived carbon framework was buried inside nanocrystalline SnO2 thin film as an electron highway to increase the transporting rate of electrons in QD-sensitized thin film. Abstract : Metal–organic-framework (MOF) derived carbon materials have attracted particular attention in recent years as a new class of porous conducting materials because of their well-connected networks, and tunable and versatile porosities. Herein, we report on a novel porous MOF-derived carbon framework supported PbS quantum dot-sensitized solar cells (QDSSCs). A zeolitic-imidazole framework (ZIF) layer is prepared by printing ZIF-67 powders, followed by the careful carbonation in N2 . Then nanocrystalline SnO2 thin film is coated and PbS quantum dots (QDs) are further deposited to form a PbS QD-sensitized porous conducting framework supported nanocrystalline SnO2 thin film. The morphologies and microstructure of the porous conducting framework were characterized in detail by the measurements of XRD, SEM, TEM, Raman spectrum and BET. Prior to deposition of PbS QDs, a compact TiO2 layer is modified on the sites of the porous conducting framework uncovered by SnO2 nanoparticles. The porous conducting framework is beneficial to the electron transporting process in the nanocrystalline thin film, while the compact TiO2 layer effectively suppresses the recombination of the transported electrons. The photovoltaic performance of QDSSCs is greatly improved due to the introduction of the porous conducting framework and the corresponding TiO2 compact layer. Eventually, the porous conducting framework buried in the nanocrystalline thin film improves light-to-electric conversion efficiency by 2.5 times compared with that of the cell without the porous carbon framework.